HISTOCHEMICAL INVESTIGATION OF TRICHOMES AND CHEMICAL COMPOSITION OF ESSENTIAL OIL FROM Euphrasia stricta D. Wolff ex J.F. Lehm. (OROBANCHACEAE) - Weronika Haratym; Elżbieta Weryszko-Chmielewska (Acta Scientiarum Polonorum: Hortorum Cultus, 2017)
Micromorphological and anatomical investigations of trichomes on vegetative and generative organs of the drug eyebright (Euphrasia stricta D. Wolff ex J.F. Lehm.) were carried out. Additionally, identification of the main components of the secreted products was conducted. The following types of glandular structures were found: capitate trichomes (i) with a unicellular head, a neck cell, and a 2-celled stalk, (ii) with a unicellular head, a neck cell, and 3-celled stalk, (iii) with a bicellular head and sporadically with a 3- or 4-celled head; moreover, on the surface of corolla unicellular and 2–3-celled clavate trichomes, ribbon-like trichomes, and papillae were present. Using fluorescence microscopy and histochemical tests, various substances such as lipids, phenolic compounds, terpenes containing steroids, terpenoids, sesquiterpenes, tannins, and flavonoids were determined but only in the capitate trichomes. The analysis of the essential oil showed that its content in the dry herb of E. stricta was on average 0.257%. Gas chromatography revealed the presence of 28 compounds.